Effects of Land Use Types and soil Depths on Soil Organic Carbon and Total Nitrogen Stocks of Karacabey Floodplain Forests in Northwest Turkey - Sariyildiz, Temel; Aygun, Derya Ozcelik; Parlak, Salih; Tani, Mert (Springer, 2022)
To evaluate soil organic carbon (SOC) and total nitrogen (TN) stocks of ash, alder and oak tree stands in Karacabey floodplain forest and adjacent Calabrian pine forest, grassland, cropland and sand dune in relation to soil depths (0-130 cm), a study in three replicate sites for each tree and the adjacent sites was carried out in northwest Turkey. The results indicated that among the tree species, alder stands had the greatest SOC (3.97%) and TN (0.328%) and total accumulation of SOC (405 Mg ha(-1)) and TN (34.4 Mg ha(-1)), followed by ash tree (3.11%, 0.302%, 393 Mg ha(-1) and 26.2 Mg ha(-1) respectively) and oak (2.43%, 0.220%, 293 Mg ha(-1) and 28.6 Mg ha(-1) respectively). However, the grassland showed the highest cumulative SOC densities within 0-130 cm depth (678 Mg ha(-1)) compared to the tree species. It also showed higher TN densities (27.5 Mg ha(-1)) than the ash tree and the Calabrian pine stands, whereas lower than the alder and oak stands. The sand dunes showed the lowest SOC and TN values. Compared to the soil depth of 0-30 cm, mean SOC and TN stored in 30-130 cm soil depth accounted for 58% and 40% in ash stands, 41% and 45% in alder stands, 52% and 56% in oak stands, 57% and 66% in Calabrian pine stands respectively. Thick alluvial soil and dry climate in the region could be responsible for the better root system development, and thus much higher SOC and TN stocks into deeper soil layers.
Keywords: Floodplain forests; Carbon stocks; Land-use types; Soil depths